Rancangan Sistem Informasi Penelitian Di Politeknik TEDC Bandung - Ekawati, Nia; Lestari, Dina Shinta (Journal of Informatics and Electronics Engineering; Vol 3 No 1 (2023): Juni 2023DO - 10.70428/jiee.v3i1.720, 2023)
A good and quality education in a university is to carry out Tridharma Perguruan Tinggi activities regularly, one of these activities is research. Research is very useful and helps to improve the quality of education in a university. The scientific repertoire of each lecturer is certainly different, meaning that the researches that exist in the Higher Education environment have different diversity. Research in the Bandung TEDC Polytechnic environment is currently quite diverse because it has 12 different sciences. However, the research conducted by TEDC Bandung Polytechnic lecturers has not met expectations, it still needs improvement in terms of facilities and infrastructure for research activities. One of them is an Information System for managing Research in the Bandung TEDC Polytechnic environment. The purpose of this research is how to design a research information system at the Bandung TEDC Polytechnic, while the method used in this research is an Object Oriented Technology method. Based on the research objectives previously described, the results of the research at this time are designs that are made according to the needs as a means and infrastructure for Lecturer Research activities. It can be concluded that the design that has been made can facilitate the preparation of facilities and infrastructure in the Bandung TEDC Polytechnic environment.